2018
DOI: 10.1021/acscatal.8b01877
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies of a Flavin Monooxygenase: Sulfur Oxidation of Dibenzothiophenes by DszC

Abstract: Flavin monoxygenases (FMOs) are enzymes of increasing biotechnological (e.g., crude oil biodesulfurization) and pharmacological (e.g., drug metabolism) interest that perform the oxidation of soft nucleophiles and play key roles in the excretion of xenobiotics or in sulfur amino acid metabolism. DszC is a key FMO involved in sulfur oxidation of dibenzothiophenes (DBTs) through the 4S metabolic pathway of some bacteria. This pathway can be a cheaper and greener alternative for sulfur removal, as DBTs are the maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 95 publications
(177 reference statements)
3
32
0
Order By: Relevance
“…Here, we aim to understand the intricacies of the electrophilic aromatic substitution mechanism of DszB using molecular dynamics (MD) and quantum mechanics/molecular mechanics (QM/MM) methods, within the ONIOM formalism, using a similar methodology applied to other enzymes of this pathway. ,, After constructing a suitable QM/MM model, we followed this mechanism with the enzyme in many different conformations to better understand the relationship between the active site preorganization and the activation barrier. , The results shed light on the mechanism of the whole catalytic cycle and the preorganization determinants that promote the emergence of low activation barriers.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we aim to understand the intricacies of the electrophilic aromatic substitution mechanism of DszB using molecular dynamics (MD) and quantum mechanics/molecular mechanics (QM/MM) methods, within the ONIOM formalism, using a similar methodology applied to other enzymes of this pathway. ,, After constructing a suitable QM/MM model, we followed this mechanism with the enzyme in many different conformations to better understand the relationship between the active site preorganization and the activation barrier. , The results shed light on the mechanism of the whole catalytic cycle and the preorganization determinants that promote the emergence of low activation barriers.…”
Section: Introductionmentioning
confidence: 99%
“…However, later, a positively charged residue around the flavin was found to be recurrent but crucial for maintaining the reactivity of flavin-dependent proteins . Specifically, the PCET is put forward in some specific flavin-dependent oxidases and mono-oxygenases, ,, which provide a new view for oxygen activation in flavin chemistry. In the PCET mechanism, the electron transfer (step 1 in the SET mechanism) is coupled with the proton transfer (step 3 in the SET mechanism).…”
Section: Resultsmentioning
confidence: 99%
“…In most investigated flavin-dependent proteins, the oxygenation reaction follows the multiple site-electron proton transfer mechanism, which is a special PCET pathway where the electron–proton acceptor (oxygen for this case) simultaneously accepts the electron and the proton from different donors (reduced flavin and some residue). The positively charged residue is the proton source. ,,, So the mutations of the vital residue would result in a dramatic decrease in reactivity. As discussed above, for the oxygenation reaction of free reduced flavin, the proton is transferred from the reduced flavin itself to the oxygen because there are no other proton sources. Therefore, the reaction kinetics of oxygen activation in flavin-dependent proteins and in bulk solutions vary considerably. , Additionally, it has been reported that the hydrogen bond connecting to N 5 of the flavin can stabilize the oxygenated intermediate in flavin-dependent proteins. , So it is rational to speculate that the oxygenated product from self-proton transfer of free reduced flavin is less stable than it is in the protein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The K I values of the DszC mutants were slightly higher than that of the WT protein, indicating that their substrate inhibition was alleviated (Table 2). The DszC substrate binding pocket has been previously described in detail, [33][34][35][36]43 and the HBP binding site should not be the same as the substrate binding site because the inhibition of DszC by HBP is noncompetitive. 23 Although the true HBP binding site could not be verified in this study, the acquisition of the AKWC mutant made a significant contribution to the feedback inhibition desensitization of DszC.…”
Section: Acs Synthetic Biologymentioning
confidence: 99%